2009
DOI: 10.1038/nature08162
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive chromatin in human sperm packages genes for embryo development

Abstract: SummaryAs nucleosomes are widely replaced by protamine in mature human sperm, epigenetic contributions of sperm chromatin to embryo development have been considered highly limited. However, we find the retained nucleosomes significantly enriched at loci of developmental importance including imprinted gene clusters, miRNA clusters, HOX gene clusters, and the promoters of stand-alone developmental transcription and signaling factors. Importantly, histone modifications localize to particular developmental loci. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
1,228
4
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,186 publications
(1,327 citation statements)
references
References 39 publications
52
1,228
4
14
Order By: Relevance
“…As we discussed in the ‘Introduction’ section, there exists some disagreement in the mapping of sperm nucleosome-retaining regions. In the first human dataset (17) the retention prevalence of developmental promoters over the gene poor regions was suggested. Later, a study that utilized fixed chromatin and a smaller amount of micrococcal nuclease concluded that there is a prevalence of the gene-poor regions in the nucleosome fractions (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we discussed in the ‘Introduction’ section, there exists some disagreement in the mapping of sperm nucleosome-retaining regions. In the first human dataset (17) the retention prevalence of developmental promoters over the gene poor regions was suggested. Later, a study that utilized fixed chromatin and a smaller amount of micrococcal nuclease concluded that there is a prevalence of the gene-poor regions in the nucleosome fractions (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…These nucleosome-protected regions are of great interest because they can potentially mediate transgenerational epigenetic inheritance. The first high-resolution genome-wide map of human spermatozoa histones shows a strong enrichment in methylated histone H3K4me3 at many promoters of developmental genes, genes encoding signaling factors, imprinted gene clusters, microRNA and HOX gene clusters (17). These studies showed that the promoters in sperm are enriched in H3K4me3 and H3K27me3, and it was suggested that genes with these marks play a particularly important role in epigenetic inheritance (1618).…”
Section: Introductionmentioning
confidence: 99%
“…Even where the seminal parameters are normal, ejaculates showing sperm with high DNA damage have been reported 10, 11. Moreover, various epidemiological studies reporting the methylation status of imprinted genes of sperm from severely infertile men show a significant risk of imprinting disorders in offspring conceived by IVF and ICSI 18, 19, 20, 21, 22, 23, 24, 25, 26. These observations strongly argue that the sperm genome provides an epigenetically poised set of developmental genes that potentially have a crucial effect on embryological growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that imprinted loci retain histones in mature sperm, raising the possibility that histone modification can be an imprint. 34 Notably, H3K4me3 is enriched at regions with no methylation in sperm, suggesting that this mark might protect the oocyte-methylated ICRs from methylation in the male germline. 34,35 Figure 1 Chronology of genomic imprinting and various factors involved in the two major steps, establishment and maintenance.…”
mentioning
confidence: 99%